Engineered Molecular Chain Ordering in Single‐Walled Carbon Nanotubes/Polyaniline Composite Films for High‐Performance Organic Thermoelectric Materials. Issue 12 (27th May 2016) - Wang, Liming; Yao, Qin; Xiao, Juanxiu; Zeng, Kaiyang; Qu, Sanyin; Shi, Wei; Wang, Qun; Chen, Lidong
Abstract: Single‐walled carbon nanotubes (SWNTs)/polyaniline (PANI) composite films with enhanced thermoelectric properties were prepared by combining in situ polymerization and solution processing. Conductive atomic force microscopy and X‐ray diffraction measurements confirmed that solution processing and strong π–π interactions between the PANI and SWNTs induced the PANI molecules to form a highly ordered structure. The improved degree of order of the PANI molecular arrangement increased the carrier mobility and thereby enhanced the electrical transport properties of PANI. The maximum in‐plane electrical conductivity and power factor of the SWNTs/PANI composite films reached 1.44×10 3 S cm −1 and 217 μW m −1 K −2, respectively, at room temperature. Furthermore, a thermoelectric generator fabricated with the SWNTs/PANI composite films showed good electric generation ability and stability. A high power density of 10.4 μW cm −2 K −1 was obtained, which is superior to most reported results obtained in organic thermoelectric modules. Abstract : PANI for your thoughts : Single‐walled carbon nanotubes (SWNTs)/polyaniline (PANI) composite films with enhanced thermoelectric properties are prepared by combining in situ polymerization and solution processing. Strong π–π interactions induce the PANI molecules to form a highly ordered structure, which improves carrier mobility and thereby enhances electrical transport.